Development of a waste management protocol based on assessment of knowledge and practice of healthcare personnel in surgical departments - Mostafa, Gehan M.A.; Shazly, Mona M.; Sherief, Wafaa I. (Waste management (Elmsford), 2009)
Good healthcare waste management in a hospital depends on a dedicated waste management team, good administration, careful planning, sound organization, underpinning legislation, adequate financing, and full participation by trained staff. Hence, waste management protocols must be convenient and sensible. To assess the knowledge and practice related to waste management among doctors, nurses, and housekeepers in the surgical departments at Al-Mansoura University Hospital, and to design and validate a waste management protocol for the health team in these settings. This cross-sectional study was carried out in the eight surgical departments at Al-Mansoura University Hospital. All health care personnel and their assistants were included: 38 doctors, 106 nurses, and 56 housekeepers. Two groups of jury were included for experts’ opinions validation of the developed protocol, one from academia (30 members) and the other from service providers (30 members). Data were collected using a self-administered knowledge questionnaire for nurses and doctors, and an interview questionnaire for housekeepers. Observation checklists were used for assessment of performance. The researchers developed the first draft of the waste management protocol according to the results of the analysis of the data collected in the assessment phase. Then, the protocol was presented to the jury group for validation, and then was implemented. Only 27.4% of the nurses, 32.1% of the housekeepers, and 36.8% of the doctors had satisfactory knowledge. Concerning practice, 18.9% of the nurses, 7.1% of the housekeepers, and none of the doctors had adequate practice. Nurses’ knowledge score had a statistically significant weak positive correlation with the attendance of training courses ( r = 0.23, p < 0.05). Validation of the developed protocol was done, and the percent of agreement ranged between 60.0% and 96.7% for the service group, and 60.0% and 90.0% for the academia group. The majority of the doctors, nurses, and housekeepers have unsatisfactory knowledge and inadequate practice related to health care waste management. The knowledge among nurses is positively affected by attendance of training programs. Based on the findings, a protocol for healthcare waste management was developed and validated. It is recommended to implement the developed waste management protocol for the surgical departments in the designed hospital, with establishment of waste management audits.